Women's emotion work in the context of intimate partner sexual violence - Tarzia, Laura (Journal of family violence, 2021)
Intimate partner sexual violence (IPSV) is a serious and prevalent form of violence against women. Yet, it has been neglected in research, policy and practice. In particular, the complex dynamics of IPSV are poorly understood, and qualitative research is lacking. This paper explores women’s emotional responses and coping strategies in the context of IPSV, using the sociological concept of “emotion work” to make sense of their experiences. Emotion work refers to the emotional labour undertaken by individuals to try and shape their own and others’ emotional responses. It can take the form of “deep acting” where the individual convinces themselves that an emotional response is authentic, or “surface acting” which is more performative. In-depth, unstructured interviews with survivors were utilized to explore their lived experiences of IPSV. Reflexive thematic analysis was used to develop key themes. Three main themes were developed: 1) “Trying to make things work in the bedroom”, describes the deep acting women undertook to convince themselves that their own sexual deficiencies were to blame for the abuse. It also highlights the emotion work of protecting their partner’s feelings; 2) “Faking pleasure, minimizing worries” demonstrates how women began to acknowledge, but still minimized the abuse (deep acting) and faked pleasure as a safety strategy (surface acting); 3) “Protecting myself from the worst of it” primarily explores the deep acting undertaken to emotionally detach themselves from the inevitable sexual abuse. These themes demonstrate shifts in women’s emotion work over time, corresponding to their level of awareness of the abuse. Emotion work is undertaken largely as a protective or coping mechanism for women experiencing IPSV, however, it can also function as a barrier to awareness. This has important implications for practitioners working with victim/survivors.